Clinical utility and diagnostic value of tumor-educated platelets in lung cancer: a systematic review and meta-analysis - Wiyarta, Elvan; Nugraha, Darrin Ananda; Ramadani, Muhammad Indera; Gustya, Gita Fajri; Ammar, Muhammad Farrasy; Edwar, Hana Dzakira; Kheirizzad, Nildza; Mukhlisah, Mutiah Nurul; Burhan, Erlina; Syahruddin, Elisna (Frontiers in Oncology, 2023)
Background The review addresses the knowledge gap concerning the diagnostic value and clinical utility of tumor-educated platelets (TEPs) in adult patients with lung cancer. Methods We searched twelve databases: PubMed, CENTRAL, EMBASE, CINAHL, MEDLINE, Scopus, ProQuest, MedRxiv, BioRxiv, SSRN, Clinicaltrials.gov, and CNKI up to 24 March 2023, to include any diagnostic study regarding TEPs and LC. TEPs diagnostic value was evaluated from pooled sensitivity and specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and the area under the curve (AUC). QUADAS 2 was used to assess the risk of bias. Heterogeneity analysis was assessed using the receiver operating characteristic (ROC) plane, Galbraith plot, bivariate boxplot, sensitivity analysis, and meta-regression. TEPs clinical utility was evaluated from Fagan’s nomogram. Results 44 reports from 10 studies, including 7,858 events and 6,632 controls, were analyzed. The pooled sensitivity, specificity, PLR, NLR, and DOR were 0.80 (95% CI 0.79–0.80), 0.69 (95% CI 0.69–0.70), 2.92 (95% CI 2.50–3.41), 0.26 (95% CI 0.21–0.32), and 12.1 (95% CI 8.61–16.76), respectively. In addition, the AUC of the Summary ROC curve was 0.85 (95% CI: 0.81-0.88). The overall risk of bias was low. Heterogeneity may result from cancer stage, cancer control, measuring equipment, and RNA types across studies. There was no apparent publication bias (p=0.29) with significant positive (79%) and negative (22%) post-test probability, according to Deeks funnel plot asymmetry test and Fagan’s nomogram. Conclusion TEPs could be a moderately effective candidate biomarker for LC diagnosis.